Location-based service using ontology-based semantic queries: A study with a focus on indoor activities in a university context. (March 2017) - Lee, Kangjae; Lee, Jiyeong; Kwan, Mei-Po
Abstract: Much research on three-dimensional (3D) indoor geographic information systems (GIS) to date has been focused on 3D topological modeling in the context of emergency management and response. Besides emergency situations, however, little is known about other human activities and the effective use and retrieval of semantically relevant information about such activities based on route analysis in complex buildings regarding 3D indoor GIS. This study proposes a location-based service (LBS) using ontology-based semantic queries with a focus on the indoor activities in a university context. An ontology model called 'University activity ontology' is designed with regard to the indoor activities at a university for sharing, managing and querying data semantically. In particular, reasoning rules are created for semantic queries to retrieve and provide information about places relevant to a destination with keywords given by users. A 3D network-based topological data model is generated by connecting a road network model and indoor topological network model to calculate the shortest path from an outdoor/indoor location to an indoor destination of interest selected by users among suggested choices. For the implementation, a location-based GIS application is developed based on the Android operating system (OS) with interactive two-dimensional (2D) and 3D visualization. Highlights: This study proposes a location-based service (LBS) based on an ontology model. It uses the indoor activities in a university context as a case. The ontology model is designed for sharing, managing and querying data semantically. The model was implemented as a location-based application using the Android OS.